From compliment slips 'besalamano' to email: an approach to correspondence in the fund of the Archivo del Congreso de los Diputados - Ramírez Martín, Virginia (Revista General de Información y Documentación, 2020)
Letters are type of documents with a very singular significance in the activity of Parlaments. In these documents are information of legislative proposals and a diverse flows of communication. Letters are the writing evidence of the internal and external connections of the Spanish Parlament during his two centuries of History. Today, the correspondence is deeply different, although its communication skills is the same. Present paper tries to analyze its evolution from the past to complex and multiple present depart from the records conserved in the Archivo del Congreso de los Diputados.
Keywords: Letters; Correspondence; Archivo del Congreso de los Diputados; Digital Documents; Preservation